Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Penghindaran Pajak pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018 - Ningtyas, Debby Mustika; Suhendro, Suhendro; Wijayanti, Anita (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
Tax Avoidance is an effort to reduce tax but still comply with the provisions of taxation regulations, such as taking advantage of the exclusions and deductions that are allowed as well as postponing taxes that have not been regulated in the applicable tax regulations. The purpose of this study is to examine and analyze the effect of profitability, leverage, and company size on tax avoidance. The population in this study are banking companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sampling technique used was purposive sampling and obtained a sample of 37 companies. The research data were analyzed using multiple linear regression analysis using SPSS 22. The results of this study indicate that profitability has a significant effect on Tax Avoidance. Meanwhile, leverage and company size have no significant effect on Tax Avoidance.